Eco-friendly and sustainable antibacterial functionalization of medical textiles using natural dyes: a review - Ali Shams Nateri; Fatemeh Shams Nateri (Results in Chemistry)
Various antibacterial agents, including chemical agents, nanoparticles, and natural dyes, have been used to enhance the antimicrobial properties of textiles. The aim of this article is to identify the latest research in the field of antibacterial functionalization of textiles using natural dyes for medical textile applications. In addition, it addresses the challenges and research gaps in the antibacterial functionalization of textiles with natural dyes and their commercialization. The increasing interest in the application of natural dyes is because of their medicinal applications, which are beneficial not only in textiles but also in pharmaceuticals. These dyes enhance the functional characteristics of fabrics, particularly in medical applications, by providing antimicrobial benefits that are fundamental for patient care. Three conventional methods were used for dyeing textiles with natural dyes: Pre-Mordanting (two-step), Meta-Mordanting (one-step), and Post-Mordanting (two-step). Several natural dyes were used for the antibacterial functionalization of cellulosic fibers, for example cotton, viscose, linen, and hemp, as well as protein fibers like wool and silk, and synthetic fibers for example polyester and polyamide (nylon). The evaluation of antibacterial activity in textiles is governed by standardized methods from organizations like ASTM, ISO, AATCC, and JIS. This review studied various natural dyes with antimicrobial properties, highlighting their application in medical textiles, such as gauze bandages. The focus on natural dyes reflects a broader trend toward eco-friendly products in the textile industry and also supports the demand for sustainable healthcare solutions. Studies indicate that natural colorants not only produce color in textiles but also have antibacterial properties, creating them suitable for healthcare applications, such as medical textiles. This indicates that using natural dyes may be the most effective strategy for improving antibacterial effectiveness while ensuring safety and sustainability.